Molecular and crystal structure characteristics of 2-phenylaminotetrahydro-1,3-thiazepine hydrochloride and 2-phenyliminohexahydro-1,3-thiazepine - Umirov, Mukhriddin; Eshimbetov, Alisher; Ashurov, Jamshid; Turgunov, Kambarali; Khodjaniyazov, Khamid (European Journal of Chemistry, 2023)
The current research includes the synthesis and crystallographic characterization of 2-phenylaminotetrahydro-1,3-thiazepine hydrochloride (HPAT) and 2-phenyliminohexa- hydro-1,3-thiazepine (PIT) compounds. 2-Phenylaminotetrahydro-1,3-thiazepine hydro-chloride was synthesized by cyclization of 1-(4-hydroxybutyl)-3-phenylthiourea in an acidic condition. The second compound, 2-phenyliminohexahydro-1,3-thiazepine, was obtained by neutralizing 2-phenylaminotetrahydro-1,3-thiazepine hydrochloride with sodium hydrocarbonate. Both compounds were characterized by the single-crystal X-ray diffraction method. Crystal data for C11H17N2OClS (HPAT): orthorhombic, space group P212121 (no. 19), a = 4.97183(14) Å, b = 15.1169(4) Å, c = 17.7376(5) Å, V = 1333.14(6) Å3, Z = 4, μ(CuKα) = 3.859 mm-1, Dcalc = 1.299 g/cm3, 9243 reflections measured (7.684° ≤ 2Θ ≤ 152.042°), 2749 unique (Rint = 0.0314, Rsigma = 0.0255) which were used in all calculations. The final R1 was 0.0351 (I > 2σ(I)) and wR2 was 0.0911 (all data). Crystal data for C11H14N2S (PIT): monoclinic, space group P21/n (no. 14), a = 9.6303(9) Å, b = 9.8938(6) Å, c = 11.5627(9) Å, β = 103.419(8)°, V = 1071.62(14) Å3, Z = 4, μ(CuKα) = 2.357 mm-1, Dcalc = 1.279 g/cm3, 3938 reflections measured (10.798° ≤ 2Θ ≤ 152.328°), 2172 unique (Rint = 0.0288, Rsigma = 0.0330) that were used in all calculations. The final R1 was 0.0431 (I > 2σ(I)) and wR2 was 0.1219 (all data). The asymmetric unit of HPAT contains one protonated amine, one chlorine anion, and one water molecule. Chlorine anion and water molecules play the role of the bridge in chain formation along the a- and b-axis through H-bonds with N-H hydrogen atoms. Furthermore, the Hirshfeld surface analyses are performed to determine the nature of the intermolecular contacts stabilizing the crystal structures of 2-phenylaminotetrahydro-1,3-thiazepine hydrochloride and 2-phenyliminohexahydro-1,3-thiazepine.